Climate Change and Disaster Management - World Bank (World Bank, Washington, DC, 2017)
This is a background paper to the Pacific Possible report. Climate change and natural disasters represent major threats to Pacific Island countries. The report estimates the cost of climate adaptation measures for Pacific Island countries. It also proposes a range of strategies for dealing with the high uncertainty surrounding the impact of climate change over the next 25 years.